2019
DOI: 10.1186/s40880-019-0394-4
|View full text |Cite
|
Sign up to set email alerts
|

Retrieved lymph nodes from different anatomic groups in gastric cancer: a proposed optimal number, comparison with other nodal classification strategies and its impact on prognosis

Abstract: BackgroundThe optimal number of retrieved lymph nodes (LNs) in gastric cancer (GC) is still debatable and previous studies proposing new classification alternatives mostly focused on the number of retrieved LNs without proper consideration on the anatomic nodal groups’ location. Here, we assessed the impact of retrieved LNs from different nodal location groups on the survival of GC patients.MethodsStage I–III gastric cancer patients who had radical gastrectomy were investigated. LN grouping was determined acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…The fourteenth JGCA guidelines abandoned the anatomic node classification and adopted a numerical classification that includes four pN stages based on the number of mLNs much like that used in the UICC/AJCC classification [3,4]. The current Japanese guidelines were published in 2010, and since then most studies have focused on the numbers of metastatic and nonmetastatic LNs without additional consideration of the anatomical location [7,9,10]. However, basing the pN classification on the number of mLNs, regardless of their location, remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…The fourteenth JGCA guidelines abandoned the anatomic node classification and adopted a numerical classification that includes four pN stages based on the number of mLNs much like that used in the UICC/AJCC classification [3,4]. The current Japanese guidelines were published in 2010, and since then most studies have focused on the numbers of metastatic and nonmetastatic LNs without additional consideration of the anatomical location [7,9,10]. However, basing the pN classification on the number of mLNs, regardless of their location, remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Since LN metastasis is recognized as an independent prognostic factor for GC, the occurrence of LN metastasis will greatly increase the risk of postoperative recurrence and shorten postoperative survival time in EGC 2 , 11 , 12 . It was reported that EGC patients with metastasis LNs (mLNs) had more than five times the risk of postoperative recurrence than EGC patients without metastasis 11 .…”
Section: Introductionmentioning
confidence: 99%
“…12,13 The numeric LN staging system with multiple updates to the cut-off value showed high accuracy in survival prediction; however, some suggested limitations included lack of information on the anatomical extent of MLNs and the total number of LNs (TLNs) retrieved during surgery. [14][15][16][17] Son et al 14 proposed inclusion of the anatomic extent of MLNs in a staging system for more accurately predicting gastric cancer prognosis. Choi et al 18 developed an alternative LN staging system based on anatomical location, which reclassified the LN stations into lesser-curvature (LC), greater-curvature (GC), and extra-perigastric (EP) groups.…”
Section: Introductionmentioning
confidence: 99%